Role of mulching in climate-smart regenerative agriculture - Sucharita, S.; Rautaray, S. K.; Kusumavathi, K; Satapathy, B. S. (Indian Farming, 2025)
Climate change and ‘yield decline’ are the two greatest challenges for food and nutrition security. Curtailing greenhouse gas emissions, and improving the capacity to adapt and grow crops are needed to face the challenges of climate change. Similarly, to face the challenge of ‘yield decline’, organic plant nutrient supply and pest management are needed in addition to reduced tillage. Both the challenges can be solved by ‘climate smart regenerative agriculture’ (CSRA) practices such as regular addition of organic matter, covering the soil surface with vegetation wastes, avoiding intensive tillage, and least use of chemical fertilizers and pesticides. Enriching the soil organic matter pool and beneficial organisms is the key to reverse the challenges. Mulching is an important practice to fulfill these objectives with adaptive, mitigative and regenerative roles. Adaptive roles include managing high evaporation loss and irrigation demand, and moderation of soil and air temperature in microclimate. Mitigative roles include carbon sequestration and halting carbon loss from soil. Regenerative roles include enriching the carbon, nutrients, and microbes in soil, and improving the soil structure. Ultimately, crop yield is increased due to stress avoidance and favourable soil health.